Pemahaman Literasi Digital Guru PAUD Di Sekolah Bukan Sekolah Penggerak (Studi Kasus Di TK Plus An-Naafi Garut) - Ulfah, Fitria; Yusriyyah, Fida Sayyidah (LP2M STAI Al-Musaddadiyah Garut, 2025)
The use of digital media is currently a necessity in various aspects of life, including the educational aspect, where teachers are required to have an understanding and ability to utilize digital media in the learning process. This research aims to find out the extent of PAUD digital literacy teachers' understanding in schools that are not part of the driving school program. Digital skills and understanding of digital literacy for PAUD teachers have now become one of the competencies that teachers must master. The approach in this research uses a qualitative approach with a case study method, where the results of this research are a real picture of the digital literacy understanding of PAUD teachers who are not part of the driving school program. The data collection process is through observation, interviews and documentation. The data analysis technique uses Grounded Theory. The research subjects were teachers who taught at Kindergarten Plus An-Naafi Garut. The digital literacy competence of PAUD teachers needs to be improved so that they can utilize digital media as open materials well and optimally. The research results in this study regarding PAUD teachers' understanding of digital literacy are indicated to be good. This can be seen from the teacher being able to access information, select information, understand information, and disseminate information. Keyword : Teachers, Digital Literacy, Early Childhood Education